(untitled) (FABICIB, 2025)
Cystic fibrosis is the most common genetic disease in the caucasian population and is characterized by dysfunction of the exocrine glands in the body. Respiratory involvement stems from the thickening of bronchial secretions, leading to obstruction, inflammation, and chronic infection of the lower airway. Based on this pathogenic foundation, numerous exacerbations or acute superinfections occur, affecting lung function and constituting one of the most significant causes of morbidity and mortality in affected patients. The microorganisms that frequently colonize the respiratory tract of these patients are Staphylococcus aureus, Pseudomonas aeruginosa, and Haemophilus influenzae. This same order was observed in all age groups included in this study. 36.8% of S. aureus isolates were methicillin-resistant, and 11.8% exhibited resistance to erythromycin and clindamycin through the MLSBi mechanism. The highest resistance among P. aeruginosa strains was against amikacin (18.7%). 35.4% of H. influenzae isolates were resistant to ampicillin due to the presence of beta lactamases. Early treatment of respiratory complications with antimicrobials is crucial in improving the survival and prognosis of CF patients.